PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CAPCUT MATERI KEKAYAAN BUDAYA INDONESIA PADA PEMBELAJARAN IPAS UNTUK MENDUKUNG MERDEKA BELAJAR SISWA KELAS IV MIN 2 DHARMASRAYA - Estuhono Estuhono; Moh Rosyid Mahmudi; Ridho Ilahi (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research is motivated by the low student learning outcomes. Based on the results of interviews and observations on the IPAS material, many students have not achieved the general completeness criteria (KKM). This can be seen from the number of students as many as 24 students. Only 8 students whose grades passed KKM were completed with a percentage of 33.33% and whose grades were incomplete KKM as many as 16 students with a presentation of 66.66%. So from these problems the researcher wants to develop a learning video using the capcut application for Indonesian cultural material on IPAS material. This research uses the type of R&D (Reseasrch and Development) research using the ADDIE model which has 5 parts, namely: Analysis Stage, Design, Development, Implementation, and Evaluation. The type of data used is qualitative and quantitative. The instrument used is a sheet of validity, practicality, effectiveness. Data collection techniques using interview techniques, observation and documentation. Data analysis techniques carried out in this development are analysis of validity, practicality and effectiveness. Based on the effectiveness test using learning videos, students' learning outcomes have reached KKM 75. Completeness of student learning outcomes with an average of 95.75% is categorized as very effective because the video has provided results that are in accordance with the learning objectives based on the results of students' learning tests. Meanwhile, the incompleteness of students with an average of 6.25% is categorized as ineffective because the test results during the trial showed that students did not meet the minimum completeness. So that videos using the Capcut application can be applied in the learning process.